2002
DOI: 10.1118/1.1496099
|View full text |Cite
|
Sign up to set email alerts
|

Let's abandon geometry factors other than that of a point source in brachytherapy dosimetry

Abstract: Articles you may be interested inComment on "Let's abandon geometry factors other than that of a point source in brachytherapy dosimetry" [Med Limitations of the point and line source approximations for the determination of geometry factors around brachytherapy sources Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…II B͒. 24 However, the ''exact'' geometry factor will also be used in the discussion of the TG-43 dosimetric parameters dependence and variation. Table II summarizes the MC calculated dose rate constant, ⌳, of the three 60 Co HDR sources as well as a bare 60 Co point source.…”
Section: B Tg-43 Formalism Dosimetry Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…II B͒. 24 However, the ''exact'' geometry factor will also be used in the discussion of the TG-43 dosimetric parameters dependence and variation. Table II summarizes the MC calculated dose rate constant, ⌳, of the three 60 Co HDR sources as well as a bare 60 Co point source.…”
Section: B Tg-43 Formalism Dosimetry Resultsmentioning
confidence: 99%
“…Therefore, the point or line source approximations 7 are commonly used in extracting the TG-43 dosimetric parameters. Recently, Meli 24 has proposed the exclusive use of point source approximated geometry factors to eliminate the possibility of erroneous dose calculations resulting from a use of one geometry factor in a treatment planning system and another in published TG-43 parameters and ensure that Eq. ͑1͒ is used in a self-consistent manner with regard to geometry factor calculation.…”
Section: B Monte Carlo Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, specific dosimetry parameters have garnered considerable interest in the brachytherapy dosimetry community during recent years. [2][3][4][5][6] For example, dosimetry investigators have suggested both adding complexity 2 and simplifying the geometry function, G͑r , ͒, 4 toward improving brachytherapy dosimetry. The AAPM TG-43U1 currently recommends either a line-or point-source approach to approximate all commercially available brachytherapy seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Since L is primarily used to minimize interpolation errors during treatment planning, it can take on almost any value. 62,80,81 However, realistic dose distributions are usually best-approximated through using realistic L values. In practice, the geometry function is used by dosimetry investigators to determine other parameters such as g͑r͒ and F͑r , ͒.…”
Section: Vc Geometry Functionmentioning
confidence: 99%